Fish community responses to stream flow alterations and habitat modifications by small hydropower projects in the Western Ghats biodiversity hotspot, India. Issue 4 (30th May 2018) - Jumani, Suman; Rao, Shishir; Kelkar, Nachiket; Machado, Siddarth; Krishnaswamy, Jagdish; Vaidyanathan, Srinivas
Abstract: Small hydropower projects (SHPs) are promoted as environmentally benign alternatives to larger dams; however, the impacts of SHPs have been poorly studied, especially in tropical developing countries, where their growth is being encouraged. This study assessed the impacts of two SHPs on freshwater fish communities in the Western Ghats biodiversity hotspot of India. Two dammed and one undammed tributary of the Netravathi River, having similar stream order, elevation, and surrounding land‐use types, were identified as test and control sites respectively. Stream geometry, water chemistry, and fish assemblages were compared across upstream, dewatered, and downstream location categories within and across the three streams. Flow alterations induced by SHPs affected the dewatered river stretches most severely. Stream wetted width and depths diminished drastically in dammed dewatered segments, and consequently this region was characterized by elevated water temperature and reduced dissolved oxygen. Fish species composition varied significantly between dammed and undammed sites, across the upstream, dewatered, and downstream location categories. Dammed segments had lower fish species richness, diversity, and endemicity, and were dominated by eurytopic species (adapted to lentic conditions), unlike the control site, which was dominated by rheophilic species (adapted to flowing waters). Regression analyses indicated that fish species richness in dammed streams increased with distance from the dam in the upstream direction. The SHPs were found to have severe impacts on stream geometry, water chemistry, and aquatic biota, especially in the dry season. Given the ambitious targets of planned SHP growth, most of which are within ecologically fragile regions, changes in SHP operations and policies are proposed to enable the conservation of river fish diversity. These include mandatory environmental impact assessments, conserving undammed headwater streams in regulated basins, maintaining adequate environmental flows, and implementing other mitigation measures.